Determinan Produktivitas Pangan dan Konsumsi Kalori di Indonesia Tahun 2020 - Siallagan, Maria Angelika H; Rahmah, Aisyah ‘Azizah Nur; Saputra, Martino Dwi; Hidayat, Ahmad Sovi; Arthamevia, Aisha; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
One of the objectives in the Sustainable Development Goals (SDGs) agenda is to achieve the eradication of hunger, improve food security, enhance nutrition, and promote sustainable agriculture. However, environmental quality can influence the productivity and accessibility of food crops for communities. This study aims to investigate the impact of the environment on productivity and calorie consumption in 32 provinces of Indonesia using ensemble clustering and logistic regression with Penalized Maximum Likelihood Estimation (PMLE). The research findings indicate that 15 provinces in Indonesia have calorie consumption below the standard caloric sufficiency and exhibit below-average productivity for rice, corn, and chili compared to the national average. Furthermore, the logistic regression analysis with PMLE reveals that air and water quality positively and significantly influence food productivity and calorie consumption levels.